Paleoenvironmental conditions for the development of calcareous nannofossil acme during the late Miocene in the eastern equatorial Pacific. (19th March 2014) - Beltran, Catherine; Rousselle, Gabrielle; Backman, Jan; Wade, Bridget S.; Sicre, Marie Alexandrine
Abstract Repeated monospecific coccolithophore dominance intervals (acmes) of specimens belonging to the Noelaerhabdaceae family—including the genus Reticulofenestra and modern descendants Emiliania and Gephyrocapsa—occurred during the Neogene. Such acme was recognized during the late Miocene ( 8.6 Ma), at a time of a major reorganization of nannofossil assemblages resulting in a worldwide temporary disappearance of larger forms of the genus Reticulofenestra (R. pseudoumbilicus) and the gradual recovery and dominance of its smaller forms (< 5 µm). In this study we present a multiproxy investigation of late Miocene sediments from the east equatorial Pacific Integrated Ocean Drilling Program Site U1338 where small reticulofenestrid‐type placoliths with a closed central area—known as small Dictyococcites spp. (< 3 µm)—formed an acme. We report on oxygen and carbon stable isotope records of multispecies planktic calcite and alkenone‐derived sea surface temperature. Our data indicate that, during this 100 kyr long acme, the east equatorial Pacific thermocline remained deep and stable. Local surface stratification state fails to explain this acme and thus contradicts the model‐based hypothesis of a Southern Ocean high‐latitude nutrient control of the surface waters in the east equatorial Pacific. Instead, our findings suggest that external forcing such as an extended period of low eccentricity may have created favorable conditions for the small Dictyococcites spp. growth.